ST. JOHN'S WORT MAY AMELIORATE 2,4,6-TRINITROBENZENESULFONIC ACID COLITIS OF RATS THROUGH THE INDUCTION OF PREGNANE X RECEPTORS AND/OR P-GLYCOPROTEINS - (:unkn) unknown (POLISH PHYSIOLOGICAL SOC, 2015)
It is reported that deficiencies of the pregnane X receptor (PXR) and P-glycoprotein (P-gp), the latter of which is encoded by the MDR1 gene, are important factors in the pathogenesis of inflammatory bowel disease (IBD). It is also known that the activation of PXR is protective of IBD due to the mutual repression between PXR and nuclear factor kappa B (NF-kappa B) expression and because NF-kappa B was reported to play a pivotal role in the pathogenesis of ulcerative colitis. The goal of this study was to investigate whether St. John's wort (SJW) and spironolactone (SPL), both known to have strong inducing effects on cytochrome P450 (CYP) enzymes as well as PXR and P-gp, have ameliorating effects on 2,4,6-trinitrobenzenesulfonic acid (TNBS) colitis of rats through induction of PXR and/or P-gp. Wistar albino rats (250 300 g) were divided into control and TNBS-colitis groups. Each group was then divided into a) control (saline), b) SJW (300 mg/kg p.o. bid), and c) SPL (80 mg/kg p.o.) groups. Drugs were given for 7 days. Both treatments ameliorated the clinical hallmarks of colitis, as determined by body weight loss and assessment of diarrhea, colon length, and bowel histology. Plasma levels of NF-kappa B, tumour necrosis factor-alpha (TNF-alpha) and tissue myeloperoxidase (MPO) activity, as well as the oxidative stress markers that increased during colitis, decreased significantly after both treatments. The PXR and P-gp expression in the intestinal tissues was diminished in the colitis group but increased after drug treatments. Both drugs appeared to have significant antioxidant and anti-inflammatory effects and ameliorated the TNBS colitis of the rats, most likely through their PXR- and P-gp-inducing properties.
Keywords: St. John's wort; P-glycoprotein; pregnane X receptor; spironolactone; cytochrome P 450; 2,4,6-trinitrobenzenesulfonic acid; colitis; tumour necrosis factor-alpha; nuclear factor kappa B; INFLAMMATORY-BOWEL-DISEASE; EXPRESSION; GENE; RIFAXIMIN; MODEL; SPIRONOLACTONE; SUSCEPTIBILITY; DETOXIFICATION; INHIBITION; METABOLISM